2019
DOI: 10.2147/ndt.s195445
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of HAM-D scores and working ability in an observational study of Japanese patients with major depressive disorder and painful physical symptoms treated with duloxetine or SSRI monotherapy</p>

Abstract: Objective To investigate the relationship between Hamilton Depression Rating Scale (HAM-D) score and psychiatrists’ judgment of working ability in patients with major depressive disorder (MDD) and painful physical symptoms. Methods This was a prospective, observational, 12-week study in patients who received duloxetine or a selective serotonin reuptake inhibitor. Patients were ≥20 years old, resided in Japan, and had at least moderate depression (Quick Inventory of Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…A previous post hoc analysis of this study reported that a HAM-D17 total score ≤6 after 12 weeks of treatment corresponded with patients’ working ability. 13 The results of the current analysis also showed that mean HAM-D17 total score in the group with working ability recovered was less than 6 only at Week 12, although improvements of all outcome measures were observed over time in all groups. In contrast, SASS and GAF scores for social functioning were significantly higher in the working ability recovered group than in the working ability not recovered group throughout the treatment up to Week 12.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…A previous post hoc analysis of this study reported that a HAM-D17 total score ≤6 after 12 weeks of treatment corresponded with patients’ working ability. 13 The results of the current analysis also showed that mean HAM-D17 total score in the group with working ability recovered was less than 6 only at Week 12, although improvements of all outcome measures were observed over time in all groups. In contrast, SASS and GAF scores for social functioning were significantly higher in the working ability recovered group than in the working ability not recovered group throughout the treatment up to Week 12.…”
Section: Discussionsupporting
confidence: 53%
“…Full study methods and results of the primary efficacy outcome analyses, preplanned subgroup analyses, and post hoc analyses have been published previously. [11][12][13]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation